2015
DOI: 10.1186/s12978-015-0004-0
|View full text |Cite
|
Sign up to set email alerts
|

Provider attitudes about childbearing and knowledge of safer conception at two HIV clinics in Malawi

Abstract: BackgroundThere is limited understanding of health care providers’ attitudes towards HIV-infected individuals’ reproductive choices, as well as knowledge about safer conception. Our study objective was to explore provider-level factors that serve as barriers and/or facilitators to the provision of reproductive and safer conception services for men and women living with HIV.MethodsTwenty-five providers were interviewed in four focus group discussions about their attitudes regarding childbearing by HIV-infected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 32 publications
3
31
0
Order By: Relevance
“…For providers, availability was limited by: lack of training in SCSs, SCS service delivery, and preconception counselling for people living with HIV; health workforce shortages that limited the quality of counselling; poor linkages to HIV care; and lack of integration of HIV and reproductive health services (leading providers to think that SCS is someone else’s responsibility) [22, 24, 27, 35, 4751]. Studies showed that provider training and self-efficacy in talking about SCS increased SCS availability [35].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For providers, availability was limited by: lack of training in SCSs, SCS service delivery, and preconception counselling for people living with HIV; health workforce shortages that limited the quality of counselling; poor linkages to HIV care; and lack of integration of HIV and reproductive health services (leading providers to think that SCS is someone else’s responsibility) [22, 24, 27, 35, 4751]. Studies showed that provider training and self-efficacy in talking about SCS increased SCS availability [35].…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies were qualitative assessments of healthcare providers and people living with HIV or serodiscordant couples. Several studies found that providers rarely initiated discussion of fertility intentions and reproductive goals with HIV-affected clients during visits [24, 39, 41, 42, 46, 50, 58, 65]. When fertility intentions were assessed, usually only the woman’s reproductive goals were discussed and not the man’s or couples [58, 61].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While evidence-based guidelines for safer conception have been developed and tailored for settings in sub-Saharan Africa, including Kenya (Bekker et al, 2011; British HIV Association & Expert Advisory Group on AIDS, 2013; Loutfy et al, 2012; NASCOP, 2014; Panel on Treatment of HIV-Infected Pregnant Women and Prevention of Perinatal Transmission, 2010; World Health Organization, 2012), HIV care providers in Kenya and throughout the region report they are not trained in safer conception methods or counseling, and HIV-affected patients are not routinely offered safer conception information or services (Crankshaw, Mindry, Munthree, Letsoalo, & Maharaj, 2014; Finocchario-Kessler et al, 2014; Goggin et al, 2014; Kawale, Mindry, Phoya, Jansen, & Hoffman, 2015; Matthews et al, 2015). Recent guidance on pre-conception care for HIV-discordant couples in Kenya outlines various safer conception strategies for HIV-discordant couples who desire children, including initiation of antiretroviral therapy at any CD4 count, viral load monitoring and suppression, limiting condomless intercourse to the ovulatory period, semen washing, and vaginal insemination timed to ovulation (NASCOP, 2014).…”
mentioning
confidence: 99%
“…As gate-keepers of information, providers can help to ensure that clients have access to effective contraception and safer conception strategies [52]. However, numerous studies have reported that HIV providers do not routinely engage PLWH in discussions about contraception and fertility desires [35, 36, 5361], while clients rarely initiate such discussions with providers [27, 60].…”
Section: Methodsmentioning
confidence: 99%